2013
DOI: 10.1093/eurpub/ckt053
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic inequalities in Norwegian health care utilization over 3 decades: the HUNT Study

Abstract: Through the last 3 decades, the previous socio-economic differences in GP utilization have diminished. Despite this, highly educated people were more prone to utilize hospital outpatient consultations throughout the period 1984-2008.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 21 publications
3
34
0
1
Order By: Relevance
“…Inpatient care at public hospitals in Norway is free (Vikum et al . 2013). The largely semi‐decentralized structure of health care in Norway administers specialist services at the state level (since 2002) through four Regional Health Authorities and primary care services at the municipality level (Ringard et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inpatient care at public hospitals in Norway is free (Vikum et al . 2013). The largely semi‐decentralized structure of health care in Norway administers specialist services at the state level (since 2002) through four Regional Health Authorities and primary care services at the municipality level (Ringard et al .…”
Section: Introductionmentioning
confidence: 99%
“…Since 2001, nearly all Norwegian citizens have been assigned to specific regular GPs, who act as gatekeepers for specialist and elective services (Vikum et al . 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Vikum and colleagues investigated socio-economic inequalities in health care utilization from the 1980s and through the last three decades using the HUNT Study. The data suggested that previous socio-economic inequalities in GP utilization had diminished, that there was an equal utilization of in-patient care but that highly educated people were more prone to utilize hospital outpatient consultations throughout the three decades (54). Data from the Tromsø Study have largely confirmed the evidence (55).…”
Section: Social Inequalities In the Health Servicesmentioning
confidence: 90%
“…Med fastlegen som pasientenes første kontakt med helsetjenesten kan vi garantere at den norske helsetjenesten vil vaere en av de beste til å redusere sosiale ulikheter i tilgang til helsetjenester. Forskning viser at tilgang til fastlege er sosialt rettferdig, justert for behov (1). Men for å sørge for gode helsetjenester også for spesielt sårbare grupper trenger vi i tillegg spesielle ordninger, for eksempel innen rusomsorg og for personer med psykisk utviklingshemning.…”
Section: Ingvild Vatten Alsnesunclassified